Jewish Philosophy and Education: Thinking Argentina?s Diaspora from the theology of Franz Rozenzweig - Taub, Emmanuel (2015)
Latin American Jewish philosophy requires us to rethink the categories of Philosophy and Judaism. In order to articulate these two dimensions it is necessary to understand that Jewish philosophy must start from the attributes of the Jewish tradition. The matter of the education and Jewishness comes from the beginning of Judaism. Throughout the Twentieth Century, the Diaspora in Modern States acquired its peculiarities in relation to these two dimensions, education and Jewishness. Both aspects have been developed in the work of Franz Rosenzweig, one the most important Jewish philosophers of the century. The main goal of this paper is to rethink the core of Rosenzweig?s thought and his dialogues with Martin Buber and Hermann Cohen. Therefore, we will be able to explain the diaspora?s peculiarities in relation to Jewish identity and education in Latin America, especially in Argentina.